RANCANGAN TEXT EDITOR BERBASIS HURUF LONTARA - Ahmad Naswin (STMIK KHARISMA Makassar, 2017)
Language that currently used in Indonesia is Bahasa. But in every province, city, district in Indonesia have their own traditional language. Traditional language in South Sulawesi Province also there are various languages, for example Bugis language, Makassar language, and others. In this study, a text editor application is created using lontara, which can be used to edit text documents, read text documents, etc., especially in Bugis / Makassar language. As well as one effort to preserve the traditional language of Bugis / Makassar.